2021
DOI: 10.1007/s00238-021-01909-y
|View full text |Cite
|
Sign up to set email alerts
|

Who is talking about #Facelift on Instagram?

Abstract: Background The internet has become a powerful tool for disseminating medical information. Social media platforms have gained popularity among medical professionals to connect with patients and promote their work and practices. We aimed to understand who is posting about facelift procedure on Instagram. Methods Sprinklr, a social listening platform, was used to compile conversations that were posted on Instagram between January 1, 2021, and February 28, 2021, and contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(26 reference statements)
0
4
0
Order By: Relevance
“… 12 At the same time, a recent study showed that a significant portion of posts about facelift content on Instagram is made by non-health professionals. 7 Altmetrics is distinguished from other social media statistics, especially by following scientific articles on Twitter and not aiming for branding. 13 14 Any metric can be manipulated artificially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 At the same time, a recent study showed that a significant portion of posts about facelift content on Instagram is made by non-health professionals. 7 Altmetrics is distinguished from other social media statistics, especially by following scientific articles on Twitter and not aiming for branding. 13 14 Any metric can be manipulated artificially.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many analyses have recently been reported investigating metrics and their trends in the field of plastic reconstructive surgery. [7][8][9] Blepharoplasty is one of the most performed functional and esthetic operations in the world and may be an option for upper eyelids with dermatochalasis restricting visual fields, under-eye bags, tired facial appearance, and many eyelid disorders. It can also be applied at the same time as another procedure, such as a brow lift and facelift.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Private hospital and cosmetic surgeons are more likely than others to embrace social media and use it professionally. Salinas CA, 2022 10 Who is talking about #Facelift on Instagram? Eur J Plast Surg.…”
Section: Cross Sectional Studymentioning
confidence: 99%